Stand up straight! : a history of posture - Gilman, Sander L. (London, UK : Reaktion Books Ltd, 2018)
Our bodies change over time; posture is ambiguous in a number of cultural and disciplinary realms. Your posture can denote you as healthy or ill, elegant or slovenly, beautiful or ugly. Gilman examines the history and sociology of posture: how society views who we are and what we are able to do by how our bodies appear. --
Introduction: Posture beyond the workplace -- Posture in the world of movement -- Postures of the mind: theology and philosophy explain human posture -- Chest out! Posture's military meanings -- Medicine as therapy for an unhealthy posture -- Dance and the social taming of posture -- Education shapes a healthy and beautiful posture -- Anthropology remakes posture: Lamarck, Darwin and beyond -- 'Natural posture': posture and race -- 'Political posturing': posture defines the good citizen -- Contemporary posture and disability studies -- Conclusion: Maps of moral posture.
Includes bibliographical references and index.
Keywords: Posture -- History; Posture -- Social aspects